Metagenomic mining of glycoside hydrolases from the hindgut bacterial symbionts of a termite (Trinervitermes trinervoides) and the characterization of a multimodular β‐1, 4‐xylanase (GH11). (23rd May 2016) - Rashamuse, Konanani; Sanyika Tendai, Walter; Mathiba, Kgama; Ngcobo, Thobile; Mtimka, Sibongile; Brady, Dean
Abstract: In recent years, there have been particular emphases worldwide on the development and optimization of bioprocesses for the utilization of biomass. An essential component of the biomass processing conduit has been the need for robust biocatalysts as high‐performance tools for both the depolymerization of lignocellulosic biomass and synthesis of new high‐value bio‐based chemical entities. Through functional screening of the metagenome of the hindgut bacterial symbionts of a termite, Trinervitermes trinervoides, we discovered open reading frames for 25 cellulases and hemicellulases. These were classified into 14 different glycoside hydrolase (GH) families: eight GH family 5; four GH9, two GH13, and one each in GH2, GH10, GH11, GH26, GH29, GH43, GH44, GH45, GH67, and GH94 families. Of these, eight were overexpressed and partially characterized to be shown to be endocellulases (GH5C, GH5E, GH5F, and GH5G), an exocellulase (GH5D), endoxylanases (GH5H and GH11), and an α‐fucosidase (GH29). The GH11 (Xyl1) was of particular interest as it was discovered to be a multimodular β‐1, 4‐xylanase, consisting of a catalytic domain and two carbohydrate‐binding modules (CBMs). The CBM functions to selectively bind insoluble xylan and increases the rate of hydrolysis. The primary structure of GH11 showed a classical catalytic dyad of glutamic acid residues that generally forms part of the active site in GH11 enzyme family. This endoxylanase was optimal at pH 6 and 50 °C, and generated xylobiose and xylotriose from various xylan sources, including beechwood, birchwood, and wheat arabinoxylan. The catalytic ability of GH11 against natural substrate (e.g., wheat arabinoxylan) renders GH11 as a potential useful biocatalyst in the effective dismantling of complex plant biomass architecture.